National cross-sectional data on undiagnosed type 2 diabetes among adults in Ecuador - Pengpid S. (2023)
The study aimed to assess the prevalence and associated factors of undiagnosed type 2 diabetes (T2D) among adults in Ecuador. Cross-sectional data (N = 4,040, 18-69 years) who participated in the Ecuador STEPS survey in 2018, who had complete fasting blood glucose measurement. The prevalence of undiagnosed T2D was 3.7% (3.6% of total T2D), diagnosed T2D 6.7%, and total T2D 10.4%. In the adjusted multinomial logistic regression analysis, older age (50-69 years) (ARRR: 7.93, 95% CI: 3.49-18.04), obesity (ARRR: 1.90, 95% CI: 1.14-3.14), and elevated total cholesterol (ARRR: 2.05, 95% CI: 1.40-3.00) were positively associated with undiagnosed T2D versus no T2D. Older age (50-69 years) (ARRR: 5.70, 95% CI: 2.61-12.45), health care visit (ARRR: 3.12, 95% CI: 2.12-4.57), obesity (ARRR: 1.56, 95% CI: 1.02-2.40), hypertension (ARRR: 1.52, 95% CI: 1.11-2.08), and elevated total cholesterol (ARRR: 1.60, 95% CI: 1.18-2.18) were positively associated with diagnosed T2D versus no T2D. In the logistic regression analysis, only the health care visit (AOR: 0.27, 95% CI: 0.16-0.47) was negatively associated with undiagnosed T2D versus diagnosed T2D. A significant proportion of adults in Ecuador had undiagnosed T2D, and several associated factors were identified which can help in guiding interventions.